The Evolution And Impact Of E-Commerce (Journal of Namibian Studies : History Politics Culture, 2023)
This research paper delves into the evolution, current trends, and impact of e-commerce on various aspects of business and society. It examines the technological advancements that have facilitated the growth of e-commerce, the challenges faced by e-commerce businesses, and the transformative effects on consumer behavior, the economy, and regulatory frameworks. India is on the verge of a revolution in e-commerce. E-commerce, or electronic commerce, refers to the buying and selling of goods and services over the Internet. It has evolved significantly since its inception and has had a profound impact on various aspects of business, society, and the economy. Here's an overview of its evolution and impact. India's e-commerce market is expanding thanks to factors including rising smartphone adoption, rising wealth, and affordable data plans, which are fuelling the expansion of online retail. India is the second-largest internet market in the world with over 800 million users and 62 billion UPI transactions in 2022.Even though e-commerce has been popular in the nation for more than a decade, it is only in recent years that the proper ecosystem has already begun to develop. The speed of internet access, the astonishing widespread use of mobile devices, and active investment have fuelled this industry's expansion, and if present if predictions are accurate, India is on track to become the fastest-growing e-commerce in the world. India has seen a growth in the use of smartphones and the internet in recent years. Due in large part to the "Digital India" effort, there were 830 million internet connections worldwide in 2021. 55% of all connections to the internet were in metropolitan areas, and 97% of those connections were wireless. The number of smartphones has also greatly grown, and by 2026, that number is anticipated to be 1 billion. India's digital economy has benefited from this, and by 2030, it is predicted to be worth US$1 trillion.